047 Fear-Potentiated Startle and Sleep in Trauma-Exposed Men and Women with and without PTSD. (3rd May 2021) - Richards, Anne; Inslicht, Sabra; Huie, J Russell; Yack, Leslie; Straus, Laura; Felmingham, Kim; Woodward, Steve; Neylan, Thomas
Abstract: Introduction: Animal and human studies indicate that fear conditioning disrupts subsequent sleep, including REM sleep (REMS). REMS is thought to be central to fear information processing. We utilized an afternoon nap protocol to examine the effects of fear-potentiated startle (FPS), a variant of fear conditioning, on subsequent sleep integrity and REMS in trauma-exposed participants with varying levels of PTSD. We also examined the effects of changes in sleep integrity and REMS on subsequent retention and extinction of pre-sleep learning. Methods: Participants (N=47) participated in 3 nap visits. The first was an adaptation nap. The second and third nap visits were counterbalanced: a stress-condition nap, during which participants underwent FPS procedures prior to a nap and assessment of retention of fear and safety signal learning and fear extinction after the nap, and a control visit during which participants had a nap opportunity without stressful procedures. Canonical correlation analysis assessed the relationship between FPS responses and change in subsequent sleep relative to a control nap, as well as the relationship between change in sleep from control to stress condition and both subsequent fear and safety learning retention, and subsequent extinction. Results: Results demonstrated a relationship between fear learning and change in sleep and supported a relationship between safety signal learning and subsequent REMS, as well as differential conditioning and wake after sleep onset. Sleep did not predict measures of fear retention or extinction. PTSD symptoms did not predict fear learning or sleep measures. Conclusion: These findings replicate prior work showing a relationship between safety learning and REMS, suggesting that this is a core mechanism through which stress impacts fear processing. Further research is critical to further understand this effect, and to examine how different aspects of fear learning impact different components of sleep. This study also demonstrates that nap studies can be a valuable approach for studying the stress-sleep relationship. Support (if any): VA Career Development Award to Dr. Richards (5IK2CX000871-05)